Analysis of Competency and Emotional Intelligence on Employee Performance with Satisfaction As an Intervening Variable at the SEI Suka District Office Batu Bara Regency - Sri Wahyuni Nasution; Muhammad Isa Indrawan; Mesra B (Journal of Management, Economic, and Accounting, 2026)
Employee performance is an important factor in determining the success of public service delivery, especially at the sub-district level of government. The Sei Suka Sub-district Office in Batu Bara Regency, as a public service unit, still faces various performance issues, such as delays in completing work and suboptimal service quality. These conditions are thought to be influenced by factors such as competence, emotional intelligence, and employee job satisfaction. This study aims to analyze the influence of competence and emotional intelligence on employee performance with job satisfaction as an intervening variable at the Sei Suka Subdistrict Office in Batu Bara Regency. This study uses a quantitative approach with a survey method. The research population consisted of all 55 permanent employees of the Sei Suka Subdistrict Office in Batu Bara Regency, who were also used as the research sample (total sampling). Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS software. The results show that competence and emotional intelligence have a positive and significant effect on employee performance. In addition, competence and emotional intelligence also have a positive and significant effect on job satisfaction. Job satisfaction has been proven to have a positive and significant effect on employee performance and acts as an intervening variable in the relationship between competence and employee performance, as well as between emotional intelligence and employee performance. Based on these findings, it can be concluded that improving employee performance at the Sei Suka Subdistrict Office in Batu Bara Regency can be achieved through the development of employee competence and emotional intelligence, supported by efforts to increase job satisfaction. The results of this study are expected to be taken into consideration by leaders in formulating human resource management policies to improve the quality of public services in a sustainable manner.